TREVR: A generalN log² Nradiative transfer algorithm - Grond, J. J; Woods, R. M; Wadsley, J. W; Couchman, H. M. P (2019)
We present TREVR (Tree-based REVerse Ray Tracing), a general algorithm for computing the radiation field, including absorption, in astrophysical simulations. TREVR is designed to handle large numbers of sources and absorbers; it is based on a tree data structure and is thus suited to codes that use trees for their gravity or hydrodynamics solvers (e.g. Adaptive Mesh Refinement). It achieves computational speed while maintaining a specified accuracy via controlled lowering of the resolution of both sources and rays from each source. TREVR computes the radiation field in order${N\log N_{source}}$time without absorption and order${N \log N_{source} \log{N}}$time with absorption. These scalings arise from merging sources of radiation according to an opening angle criterion and walking the tree structure to trace a ray to a depth that gives the chosen accuracy for absorption. The absorption-depth refinement criterion is unique to TREVR. We provide a suite of tests demonstrating the algorithm's ability to accurately compute fluxes, ionization fronts and shadows.